Deadline - Brown, Sandra, 1948- (New York : Grand Central Publishing, 2014)
Dawson Scott is a well-respected journalist recently returned from Afghanistan. Haunted by everything he experienced, he's privately suffering from battle fatigue which is a threat to every aspect of his life. But then he gets a call from a source within the FBI. A new development has come to light in a story that began 40 years ago. It could be the BIG story of Dawson's career one in which he has a vested interest. Soon, Dawson is covering the disappearance and presumed murder of former Marine Jeremy Wesson, the biological son of the pair of terrorists who remain on the FBI's Most Wanted list. As Dawson delves into the story, he finds himself developing feelings for Wesson's ex-wife, Amelia, and her two young sons. But when Amelia's nanny turns up dead, the case takes a stunning new turn, with Dawson himself becoming a suspect.
Keywords: Women novelists -- Fiction; Murder -- Investigation -- Fiction; Family secrets -- Fiction; Romantic suspense fiction